Centro de investigación y protección de la biodiversidad (2020)
Based on an analysis of the Orinoquia and Amazonia regions, different environmental, social and economic problems are found in the department of Guaviare. In this way, an intervention is proposed at the level of the master plan in which it is intended to support and strengthen the four departments. which are: San José del Guaviare, El Retorno, Calamar and Miraflores, developing through different strategic operations, which are based on restitution, protection, connectivity and economic development. Through the analysis carried out, the department of Calamar Guaviare is taken for the development of the partial plan, which is mainly based on the protection and restoration of the environment, linking natural spaces such as agroforestry zones, forested protection zones and the connectivity of the Unilla river and its tributaries.